Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

If f(x) = −5x − 4 and g(x) = -3x - 2, find (f+ g)(x).


Sagot :

Answer:

[tex](f+g)(x) = -8x-6[/tex]

Step-by-step explanation:

We are given the two functions:

[tex]\displaystyle f(x) = -5x - 4 \text{ and } g(x) = -3x - 2[/tex]

And we want to find:

[tex](f+g)(x)[/tex]

Recall that this is equivalent to:


[tex]\displaystyle (f+g)(x) = f(x) + g(x)[/tex]

Substitute and simplify:

[tex]\displaystyle \begin{aligned} (f+g)(x) &= (-5x-4)+(-3x-2) \\ \\ &= -8x-6 \end{aligned}[/tex]

In conclusion:

[tex](f+g)(x) = -8x-6[/tex]